Impact of Narratives on Migrant Students at the Primary Level: An Analysis of NCERT English Texts (Marigold Series) from Classes I–V - Raju, Rince; Rankawat, Devendra (THE PRIMARY TEACHER, 2019)
This paper focuses on migrant students and the impact of narratives contained in NCERT primary school textbooks on these children. Today, it is not uncommon for individuals, and even families and large groups to relocate to places away from their hometowns to find work. Therefore, migration and the challenges concomitant to it, are also inevitable. In this scenario, the education of children, especially in multi-ethnic and multi-cultural classrooms, calls for delicate handling. As the NCERT follows a uniform syllabus, it is important to look at the text from the angle of migrant students as well. Such an analysis will bring out how study material can also have learning implications for children from different communities. For this purpose, this study investigates the narratives in primary school textbooks Marigold Series, NCERT and talks about the impact on migrant students.